Validation of a Typology of Religious Experience and its Relationship to the Psychotic Experience - Margolis, Robert D. (Journal of psychology and theology, 1983)
A typology of religious experience was validated and an empirical determination of the similarities between the religious and psychotic experiences was made. Expert and non-expert raters (n=16) were asked to differentiate religious experiences (n=12), fabricated religious experiences (n=12), and psychotic experiences (n=12) using the typology of religious experience. A split plot, repeated measures analysis of variance yielded three significant findings: (a) Expert raters performed significantly better than non-expert raters at identifying the three types of experiences. (b) Non-expert raters with the typology performed as well as expert raters and significantly better than non-expert raters without the typology. (c) Psychotic experiences were more easily identified than were religious or fabricated experiences.